Kinship: People and Nature in Emily Lawless’s Poetry - Hansson, Heidi (Nordic Journal of English Studies, 2014)
In both her prose writing and her poetry the Irish writer Emily Lawless (1845-1913) considers a number of environmental subjects, from mothing and dredging for shellfish and mollusks to gardening and the decline of the Irish woodland. A recurrent theme in her poetry is the concern for threatened environment, but dystopian images are balanced by portrayals of landscape as a source of spiritual wisdom and healing. Lawless’s focus is often on more insignificant examples of the natural world such as moths, crustaceans or bog-cotton rather than more conventional representations of natural beauty. Lawless was a Darwinist, and several of her poems thematise the interaction between the human and the natural world, frequently reversing the power relationship between humans and natural phenomena. A re-contextualisation of her poetry within the framework of nineteenth-century natural history, Darwinism and early ecological thought brings to the fore her exploration of the connections between nature, self and national belonging.